Erythema Dyschromicum Perstans in an 8-Year-Old Indian Child - Alexander K. C. Leung; Joseph M. Lam (Case Reports in Dermatological Medicine)
We report an 8-year-old East Indian boy with erythema dyschromicum perstans. The condition has very rarely been reported in prepubertal Indian children. A perusal of the literature revealed but two cases, to which we add another one. Recognition of erythema dyschromicum perstans in prepubertal Indian children is important for proper diagnosis and to prevent unnecessary investigations.